Laurel Wilt: A Threat to Redbay, Avocado and Related Trees in Urban and Rural Landscapes - Albert E. Mayfield, III; Jonathan H. Crane; Jason A. Smith (EDIS)
HS-1137, a 6-page illustrated fact sheet by Albert E. Mayfield III, Jonathan H. Crane, and Jason A. Smith, describes for homeowners this fungal disease of trees in the laurel family that is carried by the non-native redbay ambrosia beetle. Includes descriptions of the beetles, plant hosts, impact, host symptoms, and management strategies. Includes references. Published by the UF Horticultural Sciences Department, March 2008.